Assessing the Influence of Calcium-Based Alkaline Activators and Metakaolin on the Compressive Strength Development of Geopolymer Concrete for Different Mix Design Parameters - Midhin M.A.K.; Wong L.S.; Jasim A.M.D.A. (International Information and Engineering Technology Association, 2025)
Geopolymer concrete (GPC) represents an innovative alternative to traditional Portland cement concrete. The alkaline activators and precursors play pivotal roles in making GPC environmentally sustainable. This study delves into the positive effects of applying metakaolin (MK) as precursor in combination with an alkaline activator solution (AAS), consisting of calcium hydroxide (Ca(OH)2) and sodium silicate (Na2SiO3) on the strength enhancement. This study involves the exploration of several key factors, including water-to-solid binder ratios (W/B), Na2SiO3 to Ca(OH)2 ratios, alkaline activating solution to MK (AAS/ MK) ratios, superplasticizer dosages, MK quantities, curing temperature degrees, and heat curing durations. The objective of this article is to assess the consequences of optimizing MK with AAS on the Compressive strength (CS) of GPC. The experimental results demonstrated that optimization of GPC was achieved with a W/B of 0.75, a Na2SiO3 to Ca(OH)2 ratio of 1.5, a AAS to MK ratio of 1, a superplasticizer dosage of 1.5%, a MK quantity of 400 kg m-3, and an oven curing temperature of 80? for 24 hours, at a standard air curing duration of 28 days. Additionally, with an increasing curing age of the GPC specimens from 2 to 28 days, the CS increases from 14.74 MPa to 31.62 MPa. This reflects the successful formulation of GPC through the polycondensation process involving MK as a geopolymeric precursor and alkali polysilicates. The significance of this study lies in its contribution to the development of more environmentally friendly concrete solutions, promoting the use of alternative materials in the construction industry. Copyright: ? 2024 The author(s).